Effect of Traditional Chinese Medicine fumigation combined with acupoint massage in the prevention of deep venous thrombosis of lower limbs in elderly hospitalized patients in the Internal Medicine Department (中药熏洗联合穴位按摩预防内科老年住院患者下肢深静脉血栓形成效果观察) - DONG Fangfang (董芳芳); ZHANG Linying (张林英); HE Yan (贺艳); XU Man (许曼); LIU Zijing (刘紫荆); XIONG Qiuwan (熊秋婉) (Association of Integrative Nursing, 2023)
Objective To explore the effect of fumigation with Traditional Chinese Medicine combined with acupoint massage in the prevention of deep venous thrombosis of lower limbs in elderly hospitalized patients in the Internal Medicine Department. Methods A simple random sampling method was used to select 80 elderly inpatients (age ≥65 years old) who met the inclusion criteria in the general medical department of a certain hospital in Wuhan from June 2020 to May 2022 as the subjects of this study, and were randomly divided into control group and study group, with 40 patients in each group. The study group and the control group were treated with conventional nursing and Traditional Chinese Medicine fumigation. The study group was given acupoint massage intervention on this basis. The incidence of DVT, the change of D-dimer index in blood coagulation function and the satisfaction of patients with nursing were compared between the two groups. Results After intervention, there was no DVT reported in either group. The level of D-dimer index of the study group decreased more significantly than that of the control group(P＜0. 05). Satisfaction degree of patients in the study group was significantly higher than that of the control group(P＜0. 05). Conclusion Through improving lower limb blood flow and reducing blood hypercoagulability and D-dimer level, Traditional Chinese medicine fumigation therapy combined with acupoint massage is potentially effective in the prevention of lower limb venous thrombosis in elderly patients. (目的 探讨中药熏洗治疗联合穴位按摩预防内科老年住院患者下肢深静脉血栓形成(DVT)的效果。方法 采用简单随机抽样法, 选取2020年6月-2022年5月武汉某三级甲等中西医结合医院综合医疗科符合要求的80例老年住院患者(年龄≥65岁)为研究的对象, 随机分成对照组和研究组, 每组40名。研究组与对照组均采用常规护理及中药熏洗治疗, 研究组在此基础上给予穴位按摩干预, 比较两组干预前后DVT发生率、凝血功能中D-二聚体指标变化, 评价患者对护理服务的满意度。结果 干预后, 两组均未发生DVT。研究组D-二聚体指标较对照组下降明显, 差异有统计学意义(P＜0. 05)。研究组患者护理满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 中药熏洗治疗联合穴位按摩通过改善下肢血流、降低血液高凝状态及血液中D-二聚体水平, 预防下肢DVT。)